Youth transitions - skills, work and family formation: Preliminary findings from the round 5 survey in Ethiopia - Araya, M; Woldehanna, T; Pankhurst, A (Young Lives, 2018)
This fact sheet presents findings from the fifth round of data collection carried out by Young Lives in Ethiopia in 2016. Young Lives has followed two cohorts of children born seven years apart since 2002. This fact sheet focuses on our Older Cohort (22-year-olds in 2016) to explore issues related to education, labour market skills, employment and marriage, and how young people’s opportunities in life are influenced by their gender, their family’s wealth level, and background circumstances. This fact sheet looks at the proportion of the Older Cohort who were still in school, were working full-time, or were neither studying nor working, and the imbalance in relation to poorer groups and those from rural areas. It also looks at the proportion of the young people in our sample who were married or already had a child of their own. Finally, it identifies differences between urban and rural areas in the use of digital devices.